1984
DOI: 10.1063/1.864483
|View full text |Cite
|
Sign up to set email alerts
|

Experimental scaling laws for ablation parameters in plane target–laser interaction with 1.06 μm and 0.35 μm laser wavelengths

Abstract: Ablation parameters such as velocity, mass, momentum, pressure, and hydrodynamic efficiency have been investigated with plane targets irradiated in the range 3×1011-1015 W cm−2 with 1 nsec pulses and laser wavelengths of 1.06 μm and 0.35 μm. We show that ablation velocity, ablated mass, and momentum are in good agreement with ablation scaling laws deduced from analytical models taking into account inverse bremsstrahlung absorption below the critical density. Nevertheless, processes such as lateral conduction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 60 publications
9
32
0
1
Order By: Relevance
“…The actual plasma pressure will be higher close to the laser target, since the blow-off density is initially orders of magnitude larger than the density of the ambient plasma. Here we use an empirical scaling law for the blow-off velocity v lp ≡ 3/4v s = 2.5 × 10 7 I 0.2 12 for 1064 nm laser light, where I 12 is the intensity in units of 10 12 W/cm 2 (Key et al 1983;Meyer and Thiell 1984). While this regime is interesting in itself one can see that these conditions are not maintained long enough for a shock to form (i.e.…”
Section: Scaled Laboratory Experiments and First Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual plasma pressure will be higher close to the laser target, since the blow-off density is initially orders of magnitude larger than the density of the ambient plasma. Here we use an empirical scaling law for the blow-off velocity v lp ≡ 3/4v s = 2.5 × 10 7 I 0.2 12 for 1064 nm laser light, where I 12 is the intensity in units of 10 12 W/cm 2 (Key et al 1983;Meyer and Thiell 1984). While this regime is interesting in itself one can see that these conditions are not maintained long enough for a shock to form (i.e.…”
Section: Scaled Laboratory Experiments and First Resultsmentioning
confidence: 99%
“…Gases heavier than He are not suitable for the formation of collisionless shocks in the LAPD. At laser intensities around 10 11 W/cm 2 we expect to ablate around 10 17 particles from the laser-target (Meyer and Thiell 1984). An energy of 25 J (more than 4 times the total energy in the ambient plasma) would be sufficient to maintain the required ion-temperatures for a M A = 1 shock.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in time of ablation pressure, even for constant laser irradiation, has been first described by Caruso and Gratton [23] and later by Mora [22]. The difference between de-localized absorption and localized (at critical density) models is discussed in detail by Meyer et al [9].…”
Section: Introductionmentioning
confidence: 93%
“…These include the measurement of ablation thickness using time resolved X-ray spectroscopy [3], recoil momentum measurements [4], layered target burn trough measurements [2], time resolved X-ray radiography [1], ballistic pendula [9], Faraday cups and plasma energy calorimeters [8], and shock velocity measurements [5,6]. Here we follow the last experimental method, taking advantage of the recent advancement in the generation of high quality shocks and in the measurements of shock velocities with stepped targets [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent experiments, laser/plasma interaction studies have demonstrated the pronounced advantages of using short wavelength radiation for increased energy absorption in the plasma, reduced hot electron generation and target preheat and increased ablation rates and pressures as compared to those observed for longer wavelength experiments at similar intensities (Garban-Labaune et al 1982;Mead et al 1984;Key et al 1983;Nishimura et al 1981;Yaakobi et al 1981;Meyer & Thiell 1984). Since, the overall potential electrical efficiency of KrF laser systems is predicted to be of the order of 5 to 10%, which is much greater than any other available laser system in the UV, KrF lasers have become one of the primary candidates for a feasible fusion driver to achieve energy breakeven.…”
Section: Introductionmentioning
confidence: 96%